“Complete Venous Shutdown:” A Rare Case of Combined Superior Vena Cava (SVC) and Inferior Vena Cava (IVC) Occlusion - M. Kasim Malik; Wajahat Humayun; Amir Darki (Case Reports in Vascular Medicine)
Independently, superior vena cava (SVC) occlusion and inferior vena cava (IVC) occlusion are usually seen in the setting of SVC syndrome and iliocaval venous obstruction (ICVO), respectively. Concomitant occlusion of the SVC and IVC is rare and most commonly seen in the setting of malignancy or other hypercoagulable states. Venous hypertension can lead to the formation of “downhill” varices in the esophagus and can be a rare source of gastrointestinal bleeding. We present a rare case of combined SVC and IVC occlusion and its management.